An analysis on importance of unlocking hidden savings in procurement process in private sector in Bangladesh - Nazim, Nahid (BRAC University, 2017)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.